Composite hydrogel microspheres with excellent cell adhesion properties, their preparation methods and applications
Compound hydrogel microspheres were prepared by combining glutathione-modified silk fibroin and methacrylic anhydride-modified hyaluronic acid, which solved the problems of uneven cross-linking density and insufficient biocompatibility in the prior art, achieved excellent structural stability and cell adhesion performance, and were suitable for a variety of biomedical applications.
Patent Information
- Application Number
- CN202411918537.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the prior art, silk fibroin modified with methacrylate is difficult to control the degree of crosslinking during free radical polymerization, resulting in uneven crosslinking density, affecting biocompatibility and degradation rate, and excessively crosslinked materials may become too hard and lose their natural flexibility.
By modifying silk fibroin using glutathione, thiol-modified silk fibroin was prepared, hyaluronic acid was modified in combination with methacrylic anhydride, carbon-carbon double bonds were introduced, and composite hydrogel microspheres were formed. This method improves mechanical properties and biocompatibility by precisely controlling crosslink density, and enhances structural stability and cell adhesion properties by adding lactonic acid.
The prepared composite hydrogel microspheres have good biocompatibility and biodegradability, excellent structural stability and cell adhesion performance. They are suitable for a variety of biomedical applications and can be stored for a long time, making them easy to carry and use.
Smart Images

Figure CN119350663B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical materials, and in particular to a composite hydrogel microsphere with excellent cell adhesion performance, a preparation method and application thereof. Background Art
[0002] Hydrogel is a material composed of a polymer network and a large amount of water. The polymer chains in the hydrogel form an open network structure through physical or chemical cross-linking. This structure can absorb and retain a large amount of water, has good flexibility and elasticity, and plays a huge role in simulating biological tissues. In recent years, microgels have become a popular bioprinting structure in the fields of cell therapy, controlled drug release, disease modeling, etc. Among them, micro-hydrogels are hydrogel particles. Compared with traditional large-volume hydrogels, micro-hydrogels allow shear-thinning behavior through small-gauge needle injection and allow mixing of multiple micro-hydrogel components with different compositions, sizes and contents to create customized materials with adjustable properties.
[0003] Silk fibroin has been widely used in tissue engineering and regenerative medicine due to its adjustable physicochemical properties, excellent cell compatibility, low inflammatory characteristics and excellent mechanical properties. Hyaluronic acid is the main component of connective tissues such as extracellular matrix and synovial fluid, and plays an important physiological role in water retention, maintaining extracellular space, regulating osmotic pressure, lubrication, etc. In the prior art, there are many hydrogels with silk fibroin and hyaluronic acid as the main raw materials. For example, CN 114075339 A provides a method for preparing a biocompatible silk fibroin hydrogel for photocuring 3D printing. The method controls the mixing ratio of hyaluronic acid-methacrylate and silk fibroin-methacrylate prepolymer solutions and ethanol treatment, so that the hydrogel has good biocompatibility and adjustable degradability.
[0004] However, it is difficult to control the degree of cross-linking in the free radical polymerization process of silk fibroin modified with methacrylate, which will lead to uneven cross-linking density, affect the consistency of silk fibroin-methacrylate, and reduce biocompatibility. When used in vivo, it may affect the degradation rate of silk fibroin-methacrylate in vivo, which may lead to too slow degradation and affect biodegradability. At the same time, over-cross-linked silk fibroin-methacrylate may become too hard and lose the natural flexibility of silk fibroin. Summary of the invention
[0005] The present invention is made to solve the above-mentioned problems, and aims to provide a composite hydrogel microsphere with excellent cell adhesion performance, a preparation method and application thereof. The preparation method of the composite hydrogel microsphere adopts glutathione to modify silk fibroin, the modification reaction conditions are mild and controllable, and the prepared composite hydrogel microsphere has good biocompatibility and biodegradability.
[0006] The first aspect of the present invention provides a method for preparing composite hydrogel microspheres with excellent cell adhesion performance, characterized in that it comprises the following steps:
[0007] (1) Glutathione was used to modify silk fibroin to obtain sulfhydryl-modified silk fibroin SF-GSH;
[0008] (2) Using methacrylic anhydride as a double bond introduction agent, methacrylate groups are introduced into hyaluronic acid to form carbon-carbon double bonds, thereby obtaining double-bond-modified hyaluronic acid HA-MA;
[0009] (3) Mixing thiol-modified silk fibroin SF-GSH with double-bond-modified hyaluronic acid HA-MA, and adding lactobionic acid to prepare a composite hydrogel microsphere precursor solution;
[0010] (4) preparing composite hydrogel microspheres containing lactobionic acid from a composite hydrogel microsphere precursor solution.
[0011] The present invention uses glutathione to modify silk fibroin, and the thiol groups of the prepared thiol-modified silk fibroin can form disulfide bonds with other thiol groups on the silk fibroin for more precise cross-linking, and the reaction conditions are relatively mild and controllable. At the same time, since thiol groups are common functional groups in organisms, thiol-modified silk fibroin can maintain good biocompatibility and is closer to natural silk fibroin, which is conducive to biodegradation.
[0012] Furthermore, the present invention modifies hyaluronic acid by using methacrylic anhydride and introduces carbon-carbon double bonds into the hyaluronic acid, thereby preparing hydrogel microspheres with higher cross-linking density, improving their mechanical properties and durability, and enhancing the structural stability of the hydrogel microspheres.
[0013] Furthermore, lactobionic acid is added to the composite hydrogel microspheres of the present invention. Lactobionic acid is a natural sugar acid and has certain anti-inflammatory and antioxidant properties, which can improve the biocompatibility of the hydrogel microspheres, reduce the stimulation and inflammatory response to biological tissues, and protect cells from oxidative stress damage. At the same time, lactobionic acid can further enhance the structural stability of the hydrogel microspheres by forming hydrogen bonds or ionic interactions with the polymer chains in the hydrogel.
[0014] Furthermore, since lactobionic acid has the ability to bind to specific cell surface receptors (such as asialoglycoprotein receptors on hepatocytes), composite hydrogel microspheres containing lactobionic acid can be used in targeted drug delivery systems, allowing the hydrogel microspheres to more effectively deliver drugs to specific tissues and cells.
[0015] Compared with hyaluronic acid hydrogel microspheres or hydrogels made of a single material, the composite hydrogel microspheres prepared by the preparation method provided by the present invention can be stored in a wet environment for a long time, are easy to carry and use at any time, have good biocompatibility, and will not affect cell growth. Therefore, they can be used as fillers for a variety of hydrogel matrices, achieve adhesion of different cells in a variety of matrices, and achieve different biomedical applications.
[0016] In some embodiments, in step (3), the added mass ratio of SF-GSH, HA-MA and lactobionic acid is (1-3):1:(3-40).
[0017] Since the mass ratio between SF-GSH and HA-MA directly affects the cross-linking density inside the composite hydrogel microspheres. A higher SF-GSH ratio may lead to a higher cross-linking density, thereby increasing the mechanical strength and stability of the hydrogel. On the contrary, increasing the ratio of HA-MA may reduce the cross-linking density, making the hydrogel softer and more flexible. At the same time, the swelling behavior of the hydrogel is closely related to its cross-linking density. Further, the content of lactobionic acid affects the effect of inducing cell adhesion. By adjusting the addition ratio of SF-GSH, HA-MA and lactobionic acid, the expansion degree and adhesion properties of the composite hydrogel microspheres after absorbing water can be controlled, which is very important for designing applications such as drug carriers. In the embodiment, the addition mass ratio of SF-GSH, HA-MA and lactobionic acid is controlled to be (1~3):1:(3~40) to ensure that the performance of the composite hydrogel microspheres is within the optimal range, including cross-linking density, mechanical properties, degradation properties, biocompatibility and swelling behavior, to meet the requirements of specific applications.
[0018] In some embodiments, in step (4), the particle size of the composite hydrogel microspheres is controlled to be 30 μm-200 μm.
[0019] Controlling the particle size of microspheres can meet specific application requirements, such as drug carriers, cell culture, etc. Microspheres of different particle sizes have different drug release characteristics, cell adsorption capabilities, etc.
[0020] In some embodiments, the step (1) specifically comprises: high temperature treatment of silkworm cocoons to extract silk fibroin and dialysis purification to obtain a silk fibroin solution, adjusting the pH of the silk fibroin solution to 5-7 with MES buffer, adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide for activation treatment, and then adding glutathione to modify the silk fibroin, dialysis purification after the reaction, and freeze-drying to obtain thiol-modified silk fibroin SF-GSH.
[0021] In the embodiment, the silk fibroin in the cocoon is firstly destroyed by high temperature treatment so that the silk fibroin can be released, and the non-fibrin components, such as low molecular weight impurities generated during the extraction process, such as salts and unreacted reagents, are removed by dialysis, thereby improving the purity of the silk fibroin and obtaining a relatively pure silk fibroin solution. Secondly, MES (2-(N-morpholine) ethanesulfonic acid) buffer is used to maintain the pH value of the reaction system within a suitable range to maintain the activity of the silk fibroin for subsequent activation operations. Thirdly, coupling agents 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide are used to activate the carboxyl groups on the surface of the silk fibroin, making it easier to react with glutathione. Active sites are provided for the modification of silk fibroin and glutathione (GSH) is added to modify the silk fibroin. Glutathione contains sulfhydryl (-SH) groups, which can be covalently bonded to the activated silk fibroin, thereby introducing sulfhydryl functional groups. Thiol modification can improve the biological properties of silk fibroin, increase biocompatibility and degradability. After the modification reaction is completed, dialysis is used to remove unreacted reagents and by-products to further improve the purity of the thiol-modified silk fibroin. Finally, freeze-drying is used to remove moisture from the product, maintain the structure and activity of the protein, and obtain solid thiol-modified silk fibroin SF-GSH, which is easy to store and use.
[0022] In some embodiments, the step (2) specifically comprises: dissolving hyaluronic acid in a solvent, adding methacrylic anhydride to react, reacting for 20 to 30 minutes, adjusting the pH of the reaction system to 8 to 9, reacting for 8 to 12 hours, separating and purifying to obtain double-bond modified hyaluronic acid HA-MA.
[0023] In the embodiment, hyaluronic acid is dissolved in a solvent to improve the dispersibility and reactivity of hyaluronic acid, and methacrylic anhydride is added for chemical modification, so that methacrylic anhydride and hydroxyl groups in the hyaluronic acid molecules undergo esterification reaction to introduce methacrylate groups, thereby introducing double bonds in the hyaluronic acid molecules.
[0024] Furthermore, the rate and selectivity of the esterification reaction are controlled by adjusting the pH value of the reaction system. Under acidic conditions, the reaction of methacrylic anhydride with hyaluronic acid may be inhibited. Adjusting the pH value to alkaline (8-9) can promote the hydrolysis of methacrylic anhydride to generate methacrylate groups, which then react with the hydroxyl groups of hyaluronic acid, and control the reaction time to ensure that methacrylic anhydride and hyaluronic acid react fully to improve the modification efficiency. After the reaction is completed, the system may contain impurities such as unreacted methacrylic anhydride and by-products. Impurities are removed through separation and purification steps such as dialysis, ultrafiltration, centrifugation or column chromatography to obtain high-purity double-bond modified hyaluronic acid HA-MA.
[0025] In some embodiments, the step (3) specifically includes: adding SF-GSH and HA-MA into water and mixing them, adding a reducing agent, a surfactant, and lactobionic acid for pretreatment to obtain a composite hydrogel microsphere precursor solution.
[0026] In the embodiment, sulfhydryl-modified silk fibroin (SF-GSH) and double-bond-modified hyaluronic acid (HA-MA) are mixed in water so that the two polymer materials can be evenly dispersed and interact with each other. After the two are evenly dispersed, a reducing agent is added to destroy the disulfide bonds in SF-GSH, so that SF-GSH exposes more sulfhydryl groups (-SH), which can undergo covalent cross-linking reactions with the double bonds in HA-MA, thereby promoting the cross-linking of the two polymers.
[0027] Furthermore, the addition of surfactants reduces the surface tension of water in the composite hydrogel microsphere precursor solution, helping sulfhydryl-modified silk fibroin (SF-GSH) and double-bond-modified hyaluronic acid (HA-MA) to be better dispersed in water to form a stable emulsion or suspension. In addition, surfactants can also stabilize the structure of the prepared composite hydrogel microspheres to prevent them from aggregating or precipitating during the preparation process.
[0028] Furthermore, in order to make the composite hydrogel microspheres more capable of adhering to cells, lactobionic acid is added in the embodiment. Lactobionic acid can react with the sulfhydryl groups in SF-GSH to form a stable cross-linked structure and increase the stability and mechanical strength of the composite hydrogel microspheres.
[0029] In some embodiments, the step (4) uses droplet microfluidics technology to prepare composite hydrogel microspheres, specifically comprising: using the prepared composite hydrogel microsphere precursor solution as the aqueous phase and the soybean oil and polyglycerol ricinoleate mixed solution as the oil phase, passing them into the microfluidic chip with the help of an air pump, mixing the aqueous phase and the oil phase and then shearing them into droplets, placing an ultraviolet light source at the droplet outlet for irradiation, collecting the ultraviolet light-cured droplets in a centrifuge tube, washing, centrifuging and sieving to obtain composite hydrogel microspheres containing lactobionic acid.
[0030] In the embodiment, a mixed solution of soybean oil and polyglycerol ricinoleate is used as the oil phase, which is used to form a continuous phase in the microfluidic chip to help form and stabilize the morphology of water phase droplets. At the same time, polyglycerol ricinoleate, as an emulsifier, helps to stabilize the interface between the water phase and the oil phase and prevent the droplets from agglomerating. In the embodiment, the water phase and the oil phase are respectively introduced into the corresponding channels of the microfluidic chip with the help of an air pump. In the chip, the water phase and the oil phase are mixed and sheared into uniform droplets through the microchannel structure designed by the chip, and the droplets are solidified by an ultraviolet light source, thereby accurately controlling the size and shape of the droplets.
[0031] In some embodiments, in step (4), the flow rate ratio of the water phase to the oil phase entering the microfluidic chip is 2:(1-5).
[0032] The flow rate ratio of the water phase to the oil phase affects the size and shape of the droplets formed. A higher water phase flow rate relative to the oil phase will form smaller droplets, while a lower flow rate ratio may result in larger droplets. By adjusting the flow rate ratio, the size of the hydrogel microspheres can be precisely controlled to ensure uniformity and reproducibility.
[0033] The second aspect of the present invention provides a composite hydrogel microsphere with excellent cell adhesion performance, characterized in that the composite hydrogel microsphere is prepared according to the preparation method described in the first aspect.
[0034] The third aspect of the present invention provides an application of composite hydrogel microspheres with excellent cell adhesion performance, characterized in that the composite hydrogel microspheres prepared by the preparation method described in the first aspect or the composite hydrogel microspheres described in the second aspect are used to prepare composite hydrogels, and the added volume ratio of the composite hydrogel microspheres is 20%~70%.
[0035] The fourth aspect of the present invention provides an application of composite hydrogel microspheres with excellent cell adhesion properties, characterized in that the composite hydrogel microspheres prepared by the preparation method described in the first aspect or the composite hydrogel microspheres described in the second aspect are used in materials or medicines for promoting the regeneration and repair of damaged tissues.
[0036] By implementing the above technical solution, the present invention has the following beneficial effects:
[0037] The present invention uses glutathione to modify silk fibroin, and the thiol groups of the prepared thiol-modified silk fibroin can form disulfide bonds with other thiol groups on the silk fibroin for more precise cross-linking, and the reaction conditions are relatively mild and controllable. At the same time, since thiol groups are common functional groups in organisms, thiol-modified silk fibroin can maintain good biocompatibility and is closer to natural silk fibroin, which is conducive to biodegradation.
[0038] The present invention modifies hyaluronic acid by using methacrylic anhydride, introduces carbon-carbon double bonds into the hyaluronic acid, and can prepare hydrogel microspheres with higher cross-linking density, improve the mechanical properties and durability of the hydrogel microspheres, and enhance the structural stability of the hydrogel microspheres.
[0039] Lactobionic acid is added to the composite hydrogel microspheres of the present invention. Lactobionic acid is a natural sugar acid and has certain anti-inflammatory and antioxidant properties. It can improve the biocompatibility of the hydrogel microspheres, reduce the stimulation and inflammatory response to biological tissues, and protect cells from oxidative stress damage. At the same time, lactobionic acid can further enhance the structural stability of the hydrogel microspheres by forming hydrogen bonds or ionic interactions with polymer chains in the hydrogel. Since lactobionic acid has the ability to bind to specific cell surface receptors (such as asialoglycoprotein receptors on hepatocytes), the composite hydrogel microspheres containing lactobionic acid can be used in targeted drug delivery systems, so that the hydrogel microspheres can more effectively deliver drugs to specific tissues and cells.
[0040] Compared with single hyaluronic acid hydrogel or hydrogel, the composite hydrogel microspheres prepared by the preparation method provided by the present invention can be stored in a wet environment for a long time, are easy to carry and use at any time, have good biocompatibility, and will not affect cell growth. Therefore, they can be used as fillers for various hydrogel matrices, and different cells can be encapsulated in various matrices to achieve different biomedical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is the NMR image of SF-GSH obtained in Example 1 of the present invention;
[0042] Figure 2 is the NMR image of HA-MA obtained in Example 1 of the present invention;
[0043] Figure 3 is an electron microscope image of the composite hydrogel microspheres after curing obtained in Example 1 of the present invention;
[0044] Figure 4 1 is a microscope picture of the shearing process of the PDMS chip obtained in Example 5 of the present invention, wherein Figure A is a microscope picture of the shearing process when the chip shearing cut size is 100 μm, and Figure B is a microscope picture of the shearing process when the chip shearing cut size is 200 μm;
[0045] Figure 5 1 is an optical microscope image of the composite hydrogel microspheres obtained in Example 5 of the present invention, wherein Figure A is an optical microscope image of the composite hydrogel microspheres obtained when the chip cut size is 100 μm, and Figure B is an optical microscope image of the composite hydrogel microspheres obtained when the chip cut size is 200 μm;
[0046] Figure 61 is a particle size distribution diagram of the composite hydrogel microspheres obtained in Example 5 of the present invention, wherein Figures A to E are particle size distribution diagrams of the composite hydrogel microspheres obtained when 100 chips are randomly selected for 5 times and the size of the chip cut is 100 μm, and Figures F to J are particle size distribution diagrams of the composite hydrogel microspheres obtained when 100 chips are randomly selected for 5 times and the size of the chip cut is 200 μm;
[0047] Figure 7 : is a graph of water retention efficiency of the composite hydrogel obtained in the water retention performance test of the present invention, wherein A is a composite hydrogel sample A prepared from the composite hydrogel microspheres prepared in Example 3, B is a composite hydrogel sample B prepared from the composite hydrogel microspheres prepared in Example 4, and C is a block hydrogel sample C prepared in Comparative Example 1;
[0048] Figure 8 is a biocompatibility analysis diagram of the composite hydrogel microspheres 1-4 obtained in the biocompatibility test of the present invention, wherein 1-4 refers to the composite hydrogel microspheres 1-4 prepared in Example 1-4, and negative refers to cells cultured in a common culture medium;
[0049] Fig. 9 is a graph of the cell adhesion efficiency of the composite hydrogel microspheres obtained in the cell adhesion effect test of the present invention, wherein 1-4 refers to the composite hydrogel microspheres 1-4 prepared in Examples 1-4;
[0050] Fig.10 It is a mechanical compression performance analysis diagram obtained in the mechanical compression performance test of the present invention, wherein CG refers to the composite hydrogel sample DG prepared in the mechanical compression performance test and the block hydrogel sample C prepared in Comparative Example 1. DETAILED DESCRIPTION
[0051] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.
[0052] Example 1
[0053] (1) Preparation of thiol-modified silk fibroin SF-GSH: 5 g of shredded silkworm cocoons were added to a 0.05 M Na2CO3 aqueous solution and boiled at high temperature for 20 minutes. The solution was boiled twice, washed with ultrapure water and dried; 5 g of the dried sample was transferred to a mixed solution of 32 g CaCl2, 41 ml H2O and 34 ml C2H6O, heated and stirred at 70°C for 4 h, and the cooled silk solution was dialyzed at 4°C for 3 days to obtain a purified silk fibroin solution; the solution was adjusted to pH = 6 with MES buffer, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (0.3 mol / L) and N-hydroxysuccinimide (0.5 mol / L) were added for activation for 0.5 h, and glutathione (0.18 mol / L) was added for reaction for 18 hours, and then dialyzed for two days and freeze-dried to obtain thiol-modified silk fibroin SF-GSH.
[0054] (2) Synthesis of double-bond modified hyaluronic acid HA-MA: Weigh 2 g of hyaluronic acid (HA) and dissolve it in 75 ml of water. After it is fully dissolved, add 0.4 times the volume of N,N-dimethylformamide to the HA aqueous solution and mix evenly; slowly add 1.4 ml of methacrylic anhydride at 4°C and react for 0.5 h. Then use NaOH aqueous solution to adjust the pH to 8-9 and allow to react overnight; add 0.9 g of NaCl to the reaction solution for 1 h to break the emulsion, put it into double volume of ethanol and centrifuge to obtain a precipitate. The precipitate is dissolved in water, dialyzed for three days and then freeze-dried to obtain double-bond modified hyaluronic acid HA-MA dry material.
[0055] Determination of the degree of substitution of thiol groups in silk fibroin and the degree of substitution of double bonds in hyaluronic acid: 1H NMR (Bruker AVANCEⅢ 500 MHz, Switzerland) was used to perform nuclear magnetic resonance hydrogen spectrum analysis on pure silk fibroin SF, thiol-modified silk fibroin SF-GSH prepared in Example 1, hyaluronic acid HA, and double-bond-modified hyaluronic acid HA-MA prepared in Example 1. 10 mg of SF, SF-GSH, HA, and HA-MA samples were dissolved in 1 mL of deuterated water (D2O) in a nuclear magnetic resonance tube, and the samples were characterized by nuclear magnetic resonance hydrogen spectrum. The characterization results are shown in the figure. Figure 1 , 2As shown in the figure, for HA-MA, the weak diffraction peaks observed at 1.8 ppm, 5.6 ppm and 6.1 ppm are all characteristic peaks of MA, corresponding to the methyl hydrogen on MA and the two hydrogens on the double bond carbon, respectively, which indicates that MA is successfully grafted onto the HA main chain. Compared with pure silk protein, SF-GSH has characteristic peaks of GSH at 2.17 ppm, 2.56 ppm, 2.93 ppm and 2.95 ppm, which indicates that GSH is successfully grafted onto SF, among which the two hydrogens of the methylene connected to the thiol group in GSH correspond to the peaks at 2.93 ppm and 2.95 ppm.
[0056] (3) Preparation of composite hydrogel microsphere precursor solution: 20 mg of thiol-modified silk fibroin SF-GSH, 10 mg of double-bond-modified hyaluronic acid HAMA, 1 ml of ultrapure water, 10 mg of pluronic F-127, 1 mg of TCEP·HCL, and 300 mg of lactobionic acid were mixed evenly to prepare a composite hydrogel microsphere precursor solution;
[0057] (4) Processing and preparation of composite hydrogel microspheres containing lactobionic acid: The prepared composite hydrogel microsphere precursor solution is used as the water phase, and a mixed solution of 92 wt% soybean oil and 8 wt% polyglycerol ricinoleate is used as the oil phase. With the help of an air pump, it is introduced into a polydimethylsiloxane chip with a cut size of 100 μm, and the flow rate of the oil phase and the water phase is controlled to be 5:2, so that it is sheared into droplets at the cross shear cut, and the resulting droplet size is about 40 μm; an ultraviolet light source with a wavelength of 402 nm is placed at the product outlet for irradiation, and the droplet-oil solution solidified by ultraviolet light is collected in a centrifuge tube, and washed once with a small amount of isobutanol, washed five times with a large amount of deionized water, and centrifuged through a cell sieve to obtain composite hydrogel microspheres 1 containing lactobionic acid with a size of 40 μm.
[0058] Microscopic morphology characterization of hydrogel microspheres:
[0059] The microscopic morphology of the hydrogel sample of Example 1 after drying at 40°C for 5 hours was observed using a desktop scanning electron microscope. The sample was placed and adhered to a standard section table with conductive glue attached. The surface was gold-sprayed using a conventional sputtering method. The scanning voltage was set to 15.00 kV and the magnification was adjusted to 500 times to characterize the microscopic morphology of the hydrogel microspheres. The desktop scanning electron microscope image obtained is shown in FIG. Figure 3 As shown, the microscopic morphology of the microspheres and the surface pores can be seen.
[0060] Example 2
[0061] The composite hydrogel microsphere precursor solution is configured the same as in Example 1. After being mixed evenly, it is passed into a polydimethylsiloxane chip with a 200 μm incision size, and the flow rate of the water phase and the oil phase is adjusted to 2:2, so that the size of the droplets sheared at the cross shear is about 150 μm. An ultraviolet light source with a wavelength of 402 nm is placed at the product outlet for irradiation, and the droplet-oil solution solidified by ultraviolet light is collected with a centrifuge tube, washed once with a small amount of isobutanol, washed five times with a large amount of deionized water, and centrifuged through a cell sieve to obtain a composite hydrogel microsphere 2 containing lactobionic acid.
[0062] Example 3
[0063] The preparation method of the composite hydrogel microsphere precursor solution is the same as that in Example 1, and the amount of lactobionic acid added is adjusted to 30 mg. After being mixed evenly, it is passed into a polydimethylsiloxane chip with a 200 μm incision size, and the flow rate of the water phase and the oil phase is adjusted to 2:2, so that the size of the droplets sheared at the cross shear is about 150 μm. An ultraviolet light source with a wavelength of 402 nm is placed at the product outlet for irradiation, and the droplet-oil solution solidified by ultraviolet light is collected with a centrifuge tube, washed once with a small amount of isobutanol, washed five times with a large amount of deionized water, and centrifuged through a cell sieve to obtain a composite hydrogel microsphere 3 containing lactobionic acid.
[0064] Example 4
[0065] The preparation method of the composite hydrogel microsphere precursor solution is the same as that in Example 1, and the addition amount of lactobionic acid is adjusted to 30 mg. After being mixed evenly, it is passed into a polydimethylsiloxane chip with a 100 μm incision size, and the flow rate of the water phase and the oil phase is adjusted to 5:2, so that the size of the droplets sheared at the cross shear is about 40 μm. An ultraviolet light source with a wavelength of 402 nm is placed at the product outlet for irradiation, and the droplet-oil solution solidified by ultraviolet light is collected with a centrifuge tube, washed once with a small amount of isobutanol, washed five times with a large amount of deionized water, and centrifuged through a cell sieve to obtain a composite hydrogel microsphere 4 containing lactobionic acid.
[0066] Example 5
[0067] The composite hydrogel microsphere precursor solution was prepared in the same manner as in Example 1. At different flow rate ratios of the water phase to the oil phase, the chip shearing droplets were sheared using a chip shearing opening size of 100 μm and 200 μm, respectively. The shearing process was as follows: Figure 4 As shown, Figure A is a microscope picture of the shearing process when the chip cut size is 100 μm, and Figure B is a microscope picture of the shearing process when the chip cut size is 200 μm.
[0068] The sheared droplets were produced from the receiving port and then irradiated with ultraviolet light. The morphology of the composite hydrogel microspheres was observed and photographed using an optical microscope. The morphology of the composite hydrogel microspheres is shown in the attached figure. Figure 5As shown, Figure A is an optical microscope image of the composite hydrogel microspheres obtained when the chip cut size is 100 μm, and Figure B is an optical microscope image of the composite hydrogel microspheres obtained when the chip cut size is 200 μm.
[0069] ImageJ software was used to perform five measurement experiments on the composite hydrogel microsphere images prepared using chip cut sizes of 100 μm and 200 μm, and 100 microspheres were randomly selected each time to measure their sizes. The five measurement experiments of the composite hydrogel microspheres prepared using a chip cut size of 100 μm were marked as A, B, C, D, and E, and the five measurement experiments of the composite hydrogel microspheres prepared using a chip cut size of 200 μm were marked as F, G, H, I, and J. The average particle size was calculated and the particle size distribution curve was drawn. The particle size distribution diagram of the composite hydrogel microspheres is shown in FIG. Figure 6 As shown, Figures A to E are the particle size distribution diagrams of the composite hydrogel microspheres obtained when 100 chips were randomly selected for 5 times with a chip cut size of 100 μm, and Figures F to J are the particle size distribution diagrams of the composite hydrogel microspheres obtained when 100 chips were randomly selected for 5 times with a chip cut size of 200 μm. The measured data are shown in Tables 1 and 2, which are the average particle sizes of chip cut sizes of 100 μm and 200 μm, respectively. The average particle size: .
[0070] Table 1 Average particle size of composite hydrogel microspheres when the chip cut size is 100 μm
[0071]
[0072] Table 2 Average particle size of composite hydrogel microspheres when the chip cut size is 200 μm
[0073]
[0074] Comparative Example 1
[0075] The preparation of double-bond-modified hyaluronic acid and thiol-modified silk fibroin was the same as in Example 1. 20 mg of thiol-modified silk fibroin, 10 mg of double-bond-modified hyaluronic acid, 1 ml of ultrapure water, and 1 mg of TCEP·HCL were mixed evenly to prepare a hydrogel precursor solution; the solution was poured into a 48-well plate and cured under an ultraviolet light source with a wavelength of 402 nm to obtain a block hydrogel sample C.
[0076] Performance Testing
[0077] 1. Water retention performance test:
[0078] The composite hydrogel microspheres prepared in Example 3 and Example 4 were mixed with 20 mg of thiol-modified silk fibroin, 10 mg of double-bond-modified hyaluronic acid, 1 ml of ultrapure water, and 1 mg of TCEP·HCL in a ratio of V ball: V liquid = 6:4, and evenly stirred, poured into a cylindrical mold with a thickness of 4 mm and a diameter of 17 mm, and cured under ultraviolet light of 420 nm to obtain composite hydrogel sample A prepared from the composite hydrogel microspheres prepared in Example 3 and composite hydrogel sample B prepared from the composite hydrogel microspheres prepared in Example 4, respectively. They were used as experimental groups, and the block hydrogel sample C prepared in comparative example 1 was used as the control group. The surface moisture of the three groups of samples was respectively absorbed and placed at room temperature at the same time. The weight of the hydrogel at different times within 96 hours was weighed, the results were recorded and statistically analyzed, and the water retention efficiency of the composite hydrogel microspheres was shown in the figure below. Figure 7 As shown, A is a composite hydrogel sample A prepared from the composite hydrogel microspheres prepared in Example 3, B is a composite hydrogel sample B prepared from the composite hydrogel microspheres prepared in Example 4, and C is a block hydrogel sample C prepared in Comparative Example 1. It shows that both sample A and sample B have the effect of improving the water retention performance of the hydrogel, wherein the hydrogel of sample A still retains 53.3% of its mass after 96 hours, and the hydrogel of sample B reaches 62.7% of its mass, indicating that the small particle size of the composite hydrogel microspheres is more conducive to water retention.
[0079] 2. Biocompatibility test:
[0080] The biocompatibility of the composite hydrogel microspheres 1-4 prepared in Example 1-4 was characterized by in vitro co-culture of the sample extract with L929 mouse fibroblasts using a CCK-8 kit (Cell Counting Kit-8), and cells cultured in a normal culture medium were set as a negative control group. First, the hydrogel extract was prepared by incubating the composite hydrogel microspheres 1-4 at 37 °C for 24 h at an extraction rate of 20 mg / ml in DMEM culture medium. The hydrogel extract was sterilized with a 0.22 μm filter and supplemented with 10% fetal bovine serum (FBS). L929 mouse fibroblasts (cell concentration = 1×10 4 Cells / mL) were seeded in a 96-well cell culture plate containing DMEM complete medium at 37 °C overnight. Subsequently, the medium was removed and 100 μL of the hydrogel extract was added to the culture plate. After culturing for 24 h, 48 h, and 96 h, the light absorbance (OD) value of the solution was measured at a wavelength of 450 nm using an enzyme-linked immunosorbent assay. Cell viability was calculated using the following formula:
[0081]
[0082] Where, As: absorbance of the experimental group; Ab: absorbance of the blank well; Ac: absorbance of the control group.
[0083] The test results are as follows Figure 8 As shown, 1-4 refers to the composite hydrogel microspheres 1-4 prepared in Example 1-4, and negative refers to cells cultured in ordinary culture medium. The cell survival rate of each group is about 100% per day, indicating that the composite hydrogel microspheres 1-4 prepared in Example 1-4 have no cytotoxicity and high biocompatibility.
[0084] 3. Cell adhesion effect test:
[0085] The composite hydrogel microspheres 1-4 of Examples 1-4 were selected as the experimental groups, and the average value was taken for each replicate of 3 wells. Mouse embryonic fibroblast cell line (NIH 3T3) was cultured at 5×10 4 / mL was planted in a 12-well plate, and DMEM cell culture medium containing 1.5 g / L sodium bicarbonate, 100 U / mL penicillin, 10% fetal bovine serum and 100 μg / mL streptomycin was added to each well. The well plate was placed in an incubator at 37 °C and 5% CO2 concentration until the cell confluence reached 70%. After 24 hours of culture, the number of floating cells in the culture medium was counted, the results were recorded and statistically analyzed, and the efficiency of cell adhesion of the composite hydrogel microspheres was shown in the figure. Fig. 9 As shown, 1-4 refers to the composite hydrogel microspheres 1-4 prepared in Examples 1-4. It shows that the increase in the amount of lactobionic acid added enhances the effect of inducing cell adhesion, and the microspheres with large particle size are more conducive to cell adhesion. The cell adhesion effect of the composite hydrogel microspheres 2 prepared in Example 2 can even make the cells basically completely adhere.
[0086] 4. Mechanical compression performance test:
[0087] The composite hydrogel microspheres 3 prepared in Example 3 were mixed with 20 mg of thiol-modified silk fibroin, 10 mg of double-bond-modified hyaluronic acid, 1 ml of ultrapure water, and 1 mg of TCEP·HCL in a ratio of Vsphere:Vliquid=2:8, 4:6, 6:4, and 8:2, respectively, and evenly poured into a cylindrical mold with a thickness of 4 mm and a diameter of 17 mm. The microspheres were cured under ultraviolet light of 420 nm to obtain 4 groups of composite hydrogel samples, which were numbered D, E, F, and G.
[0088] The compression properties of the above four groups of samples were measured by a high and low temperature double column tester (Instron 5966, America), and the block hydrogel C prepared in comparative example 1 was set as the control group. The compression deformation was set to 90%, the compression speed was set to 2 mm / min, and the sample was placed in the middle of the compression test table. The compression test was started when the two ends of the compression fixture table were close to the upper and lower surfaces of the hydrogel. The test was stopped when the sample was completely broken. Each group of samples was tested 3 times and the average value was taken. The compression performance of the test is as follows Fig.10 As shown, CG is the prepared composite hydrogel sample DG and the block hydrogel sample C prepared in Comparative Example 1.
[0089] As the amount of composite hydrogel microspheres added increases, the compressive strain of the material also increases, and the toughness of the material is correspondingly improved. The composite hydrogel microspheres exist as energy dissipation points to improve its mechanical properties. When the amount of composite hydrogel microspheres added reaches 80%, it will hinder the cross-linking of the hydrogel, thereby significantly reducing the compressive stress of the hydrogel.
[0090] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.
Claims
1. A method for preparing composite hydrogel microspheres with excellent cell adhesion performance, characterized in that: The following steps are involved: (1) Glutathione was used to modify silk fibroin to obtain sulfhydryl-modified silk fibroin SF-GSH; (2) Using methacrylic anhydride as a double bond introduction agent, methacrylate groups are introduced into hyaluronic acid to form carbon-carbon double bonds, thereby obtaining double-bond-modified hyaluronic acid HA-MA; (3) Mixing thiol-modified silk fibroin SF-GSH with double-bond-modified hyaluronic acid HA-MA, and adding lactobionic acid to prepare a composite hydrogel microsphere precursor solution; (4) preparing composite hydrogel microspheres containing lactobionic acid from a composite hydrogel microsphere precursor solution.
2. The preparation method according to claim 1, characterized in that: In the step (3), the added mass ratio of SF-GSH, HA-MA and lactobionic acid is (1-3):1:(3-40).
3. The preparation method according to claim 1, characterized in that: In the step (4), the particle size of the composite hydrogel microspheres is controlled to be 30 μm-200 μm.
4. The preparation method according to claim 1, characterized in that: The step (1) specifically comprises: extracting silk fibroin from silk cocoons by high temperature treatment and dialysis purification to obtain a silk fibroin solution, adjusting the pH of the silk fibroin solution to 5-7 with MES buffer, adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide for activation treatment, adding glutathione to modify the silk fibroin, dialysis purification after reaction, and freeze-drying to obtain sulfhydryl-modified silk fibroin SF-GSH.
5. The preparation method according to claim 1, characterized in that: The step (2) specifically comprises: dissolving hyaluronic acid in a solvent, adding methacrylic anhydride to react, reacting for 20 to 30 minutes, adjusting the pH of the reaction system to 8 to 9, reacting for 8 to 12 hours, separating and purifying to obtain double-bond modified hyaluronic acid HA-MA.
6. The preparation method according to claim 1, characterized in that: In the step (4), the composite hydrogel microspheres are prepared by droplet microfluidics technology, specifically comprising: using the prepared composite hydrogel microsphere precursor solution as the water phase and the soybean oil and polyglycerol ricinoleate mixed solution as the oil phase, passing them into the microfluidic chip with the help of an air pump, mixing the water phase and the oil phase and then shearing them into droplets, placing an ultraviolet light source at the droplet outlet for irradiation, collecting the droplets cured by ultraviolet light in a centrifuge tube, washing, centrifuging and sieving to obtain composite hydrogel microspheres containing lactobionic acid.
7. The preparation method according to claim 6, characterized in that: In the step (4), the flow rate ratio of the water phase to the oil phase passing into the microfluidic chip is 2:(1-5).
8. A composite hydrogel microsphere with excellent cell adhesion performance, characterized in that: The composite hydrogel microspheres are prepared according to the preparation methods described in claims 1 to 7.
9. An application of composite hydrogel microspheres with excellent cell adhesion performance, characterized in that: The composite hydrogel microspheres prepared by the preparation method of claims 1 to 7 or the composite hydrogel microspheres according to claim 8 are used to prepare composite hydrogels, and the added volume ratio of the composite hydrogel microspheres is 20% to 70%.
10. An application of composite hydrogel microspheres with excellent cell adhesion performance, characterized in that: The composite hydrogel microspheres prepared by the preparation methods of claims 1 to 7 or the composite hydrogel microspheres according to claim 8 are used in materials or medicines for promoting the regeneration and repair of damaged tissues.
Citation Information
Patent Citations
Preparation method of photo-cured 3D printing bio-compatible silk fibroin hydrogel
CN114075339A
Surface polymer brush modified hydrogel material as well as preparation method and application thereof
CN112625253A